2014
DOI: 10.1111/jam.12489
|View full text |Cite
|
Sign up to set email alerts
|

Entry of H5N1 highly pathogenic avian influenza virus into Europe through migratory wild birds: a qualitative release assessment at the species level

Abstract: Aims: To estimate qualitatively the probabilities of release (or entry) of Eurasian lineage H5N1 highly pathogenic avian influenza (HPAI) virus into Great Britain (GB), the Netherlands and Italy through selected higher risk species of migratory water bird. Methods and Results: The probabilities of one or more release events of H5N1 HPAI per year (P release ) were estimated qualitatively for 15 avian species, including swans, geese, ducks and gulls, by assessing the prevalence of H5N1 HPAI in different regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…To construct strategies to control diseases, the identification of timely risk factors in outbreaks is important (Lewallen & Courtright, 1998). Previous avian influenza epidemiologic studies have identified several risk factors from a variety of settings and countries (Abbas, Wilking, Horeth-Bontgen, & Conraths, 2012;Arriola et al, 2015;Beaudoin et al, 2014;Biswas et al, 2011;Boender et al, 2007;Bui, Gardner, MacIntyre, & Sarkar, 2017;Cao et al, 2010;Chaudhry, Rashid, Thrusfield, Welburn, & Bronsvoort, 2015;Desvaux et al, 2011;Dinh et al, 2006;Fang et al, 2008;Fasina, Rivas, Bisschop, Stegeman, & Hernandez, 2011;Gale et al, 2014;Garber et al, 2016;Gilbert et al, 2006;Henning et al, 2009;Huang, Zeng, & Wang, 2016;Iglesias, Jesus Munoz, Martinez, & de la Torre, 2010;Kung et al, 2007;Liu et al, 2015;Lohiniva et al, 2013;Loth, Gilbert, Osmani, Kalam, & Xiao, 2010;Mannelli, Ferre, & Marangon, 2006;Martin et al, 2011;McQuiston et al, 2005;Metras et al, 2013;Mounts et al, 1999;Musa, Abdu, Sackey, & Oladele, 2013;Nishiguchi et al, 2007;Osmani et al, 2014;Paul et al, 2011;Tenzin, Wangdi, & Rai, 2017;Thomas et al, 2005;Thompson, Sinclair, & Ganzevoort, 2008;…”
Section: Introductionmentioning
confidence: 99%
“…To construct strategies to control diseases, the identification of timely risk factors in outbreaks is important (Lewallen & Courtright, 1998). Previous avian influenza epidemiologic studies have identified several risk factors from a variety of settings and countries (Abbas, Wilking, Horeth-Bontgen, & Conraths, 2012;Arriola et al, 2015;Beaudoin et al, 2014;Biswas et al, 2011;Boender et al, 2007;Bui, Gardner, MacIntyre, & Sarkar, 2017;Cao et al, 2010;Chaudhry, Rashid, Thrusfield, Welburn, & Bronsvoort, 2015;Desvaux et al, 2011;Dinh et al, 2006;Fang et al, 2008;Fasina, Rivas, Bisschop, Stegeman, & Hernandez, 2011;Gale et al, 2014;Garber et al, 2016;Gilbert et al, 2006;Henning et al, 2009;Huang, Zeng, & Wang, 2016;Iglesias, Jesus Munoz, Martinez, & de la Torre, 2010;Kung et al, 2007;Liu et al, 2015;Lohiniva et al, 2013;Loth, Gilbert, Osmani, Kalam, & Xiao, 2010;Mannelli, Ferre, & Marangon, 2006;Martin et al, 2011;McQuiston et al, 2005;Metras et al, 2013;Mounts et al, 1999;Musa, Abdu, Sackey, & Oladele, 2013;Nishiguchi et al, 2007;Osmani et al, 2014;Paul et al, 2011;Tenzin, Wangdi, & Rai, 2017;Thomas et al, 2005;Thompson, Sinclair, & Ganzevoort, 2008;…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, EFSA 2012describes qualitative probabilities in terms of numerical bounds (see Table 2). There are a limited number of studies that have considered qualitative evaluation of the aggregated probability given in Equation (1) (Snary et al, 2012;Gale et al, 2014). In the examples which do exist, the estimate of probability has been undertaken subjectively, with assumptions being made on how to combine, for example a low p with a high n or a high p with a low n. To determine the most appropriate way to formalise this estimation, we break down Equation 1into separate components.…”
Section: Derivation Of a General Equationmentioning
confidence: 99%
“…However, the evaluation of the product of two qualitative probabilities has been tackled. Several matrices for this product have been published (Gale et al, 2009;Gale et al, 2010;Wieland et al, 2011;Gale et al, 2014). Of these, the matrix of Gale et al (2010) is considered most appropriate from a mathematical point of view because it is based on the premise that probabilities can only take values between 0 and 1 and that the product of two probabilities is at most, the minimum of the two values (see Table 3).…”
Section: Derivation Of a General Equationmentioning
confidence: 99%
See 2 more Smart Citations